Impacting rapid hydrogen fuel cell electric vehicle (FCEV) commercialization : system cost reduction and subcomponent performance enhancement - Wood, David L. (SAE International, 2016)
Fuel cell electric vehicles (FCEVs) powered by proton-exchange membrane fuel cells (PEFC) and fueled by hydrogen, offer the promise of zero emissions with excellent driving range and fast refueling times. FCEVs face several remaining challenges in order to achieve widespread commercialisation. Many of the challenges are addressed in this book.
Keywords: Proton exchange membrane fuel cells.; Hydrogen cars.; Hydrogen as fuel.; elektronické knihy; electronic books